2020
DOI: 10.3390/ma13214749
|View full text |Cite
|
Sign up to set email alerts
|

CNT Conductive Epoxy Composite Metamaterials: Design, Fabrication, and Characterization

Abstract: In this study, carbon nanotube (CNT) epoxy composite films were fabricated, characterized, and tested as resonant, plasmonic metamaterials. CNT–epoxy formulations, containing diverse CNT loadings, were fabricated and templates were used to generate repeating arrays of squares of diverse dimensions. Their absorption characteristics were characterized by collecting free space reflectivity data in the microwave band, using an arch setup in an anechoic chamber. Data were collected from 2 to 20 GHz. The materials b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…α could influence the polarization of electric field in CEC composite, the beneficial attenuation of microwave at α of about 45 • was caused from a viewpoint of polarization. Besides, EMI properties determined by α was also concerned with electromagnetic parameters, e.g., permittivity ε and permeability µ, which could be subjected to the influence of α in samples [26]. Herein, CEC sample with α of about 45 • exhibited more energy loss according to the dielectric loss tangent tanδ described in following section, contributing to the highest EMI SE.…”
Section: Emi Shielding Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…α could influence the polarization of electric field in CEC composite, the beneficial attenuation of microwave at α of about 45 • was caused from a viewpoint of polarization. Besides, EMI properties determined by α was also concerned with electromagnetic parameters, e.g., permittivity ε and permeability µ, which could be subjected to the influence of α in samples [26]. Herein, CEC sample with α of about 45 • exhibited more energy loss according to the dielectric loss tangent tanδ described in following section, contributing to the highest EMI SE.…”
Section: Emi Shielding Propertiesmentioning
confidence: 97%
“…Supplementary Materials Figure S8 and Figure 6 exhibited real part ε and dielectric loss tangent tanδ of the samples in the range of 8.2-12.4 GHz. Adjustable ε from positive to negative values were obtained as shown in Figure S8, these materials with negative permittivity were named as a metamaterial, which is an artificially structured material with repeatable structural pattern and is designed for specific shapes and dimensions to affect the EM wave response at a targeted wavelength/frequency [26]. To the best of our knowledge, the study of CEC composite as metamaterials was reported for the first time.…”
Section: Metamaterials Properties and Shielding Mechanismmentioning
confidence: 99%
“…In literatures, the fracture toughness of epoxy resin can be improved by the promoted dispersion of CNTs through the mechanical mixing, surface chemical modification of CNTs and the addition of surfactants. [10][11][12][13]27,43 For the mechanical mixing, the mechanical equipment, such as roll milling, extrusion, and high-shear mixing, is usually used together with the ultrasonication and solvent mixing. The process of mechanical mixing is usually complicated, the cost is high, meanwhile the carbon nanotube will be broken due to the strong mechanical shear flow.…”
Section: Fracture Toughness and Mechanismsmentioning
confidence: 99%
“…From the from the integration of Equation ( 9), estimated lifetime equal to Equation (10) for the reaction order n = 1, and Equation (11) for the reaction order n = 1.…”
Section: Lifetime Predictionsmentioning
confidence: 99%
“…The synthesis of a CNT/alumina hybrid compound has been reported in previous works [5][6][7], where its composites demonstrated good mechanical and thermal properties [8]. It is a well-known fact that CNTs possess great mechanical, thermal, electrical, and chemical properties, and can be used in polymer composites due to their unique structure [9][10][11][12]. However, their lack of dispersibility in a polymer matrix and their tendency to agglomerate with each other always hinder their original performance.…”
Section: Introductionmentioning
confidence: 97%